Transformative Social Studies Education as an Instrument for Civic Character Development in Facing Digital Social Disruption - Muhammad Farhan; Lilis Putri Handayani; Eka Putra Pratama (Journal of Social Studies Education, 2026)
The rapid development of digital technology and the emergence of increasingly complex contemporary social issues have created significant challenges for the cultivation of democratic values and tolerance among students. Social Studies Education plays a strategic role in preparing young citizens to respond to these challenges through meaningful learning experiences that connect academic knowledge with real social realities. This study aimed to examine the effectiveness of a contemporary social issues-based Social Studies learning model in strengthening democratic values and tolerance among students. The study employed a mixed-methods approach with an embedded experimental design involving secondary school students participating in Social Studies courses. The research procedure consisted of needs assessment, model development, expert validation, pilot testing, implementation, and evaluation stages. Quantitative data were collected through democratic values and tolerance questionnaires administered before and after the intervention, while qualitative data were obtained through classroom observations, interviews, reflective journals, and documentation. The findings indicated that the implementation of the learning model contributed positively to the enhancement of students’ democratic values, including participation, openness, equality, social responsibility, and respect for differing opinions. The model also improved students’ tolerance attitudes by fostering empathy, intercultural understanding, appreciation of diversity, and willingness to engage in constructive dialogue. Learning activities centered on contemporary social issues encouraged critical thinking, collaborative problem-solving, democratic deliberation, and reflective evaluation. The study concludes that a contemporary social issues-based Social Studies learning model is an effective instructional innovation for promoting democratic character and tolerance while supporting the development of active, responsible, and socially aware citizens in a pluralistic society.